How do Chinese multinationals perceive factors affecting the integration-responsiveness framework? - Fan, David; Zhu, C. (Emerald Group Publishing Ltd., 2014)
Purpose – The purpose of this paper is to clarify how Chinese multinationals perceive factors affecting the integration-responsiveness (I-R) framework. Design/methodology/approach – This study extends quantitative and conceptual studies that have clarified and assessed the underlying factors that influence multinational enterprises’ (MNEs) international business strategy choices relating to global integration and local responsiveness with the use of cross-level and in-depth interviews. Top management perceptions from nine Chinese MNEs with operations in Australia are detailed. Findings – The study obtains empirical evidence on applying the I-R framework in the context of MNEs from emerging markets. Also the hybrid factors affecting both integration and responsiveness synchronously have been confirmed by Chinese multinationals. Research limitations/implications – As a cross-sectional study, the paper focuses on senior executives’ perceptions on factors affecting the I-R framework. This analysis would be enriched by melding these perspectives with extensive secondary data on the companies concerned to assess the ratings assigned. Originality/value – When studying factors affecting global integration and local responsiveness prior studies have centred on multinationals from advanced economies and/or their subsidiaries in emerging markets. This concentration leaves unclear the relevance of developed country centred findings to MNEs from emerging markets and their subsidiaries in advanced economies, and the demonstration of how emerging markets MNEs perceive factors affecting the I-R framework. Paper type Research paper